Nippoptilia regulae ... - Ustjuzhanin, P. Ya.; Inkhavilay, Kh.; Spitsyn, V. M. (Zenodo, 2023)
Nippoptilia regulae (Meyrick, 1906) Oxyptilus regulus Meyrick, 1906: 135. (Type locality: Ceylon). MATERIAL EXAMINED. LAOS: 1♂, Attopu province, tropical forest, 14°44´08´´N, 107°29´17´´E, 8– 15.12.2022, E. Spitsyna & V. Spitsyn leg. DISTRIBUTION. Nepal, Sri Lanka, Vietnam, Australia [Gielis, 2003], Tanzania [Gielis, 2011], Thailand, Malaysia [Arenberger, 2010], Japan, Korea [Kim et al., 2010], Russia (Primorsky krai) [Ustjuzhanin et al., 2021], Sakhalin [Titova, 2022], Laos. REMARKS. First record from Laos. ... : Published as part of Ustjuzhanin, P. Ya., Inkhavilay, Kh. & Spitsyn, V. M., 2023, To the plume moths fauna (Lepidoptera:, Pterophoridae) of Laos, pp. 207-209 in Russian Entomological Journal 32 (2) on page 208, DOI: 10.15298/rusentj.32.2.11, http://zenodo.org/record/13178663 ...